LITHOLOGICAL-GEOCHEMICAL FEATURES OF THE MALINOVSKOE URANIUM DEPOSIT (RUSSIA) - Vinokurov S.F.; Doinikova O.A.; Krylova T.L.; Men'shikov V.V.; Nesterova M.V.; Ryzhov B.I.; Sysoev A.N. (My University, 2001)
The complex study of uranium ores and their host rocks of the Malinovskoe deposit revealed their specific mineralogical and geochemical peculiarities, which it differentiate them from all known ancient and recent exogenic epigenetic U deposits of the paleovalley type. Main of them represent: (1) intense repeated metasomatic chloritization and localized sulfide-selenide mineralization and carbonatization; (2) a slight manifestation of ancient ground-stratal oxidation; (3) the presence of elements in uranium ores typical both of exogenic deposits (Se, Re, Mo, V) and hydrothermal mineralization (Pb, As); (4) a distinct prevalence of coffinite and ferroselite in complex U and Se ores, respectively; (5) the significant penetrating ability and impact of U-bearing solutions; and (6) the presence of fluid inclusions, which point to mixing of thermal calcic (Mg, Fe) chloride brines with meteoric waters. These specific mineralogical and geochemical features of the Malinovskoe deposit are mainly determined by intense endogenic processes and significantly influence technological properties of ores.